Pelaksanaan Hak Tanggungan Secara Elektronik dengan Jaminan Sertipikat Tanah - Marisa, Marisa; Aminah, Aminah (Universitas Muhammadiyah Ponorogo, 2025)
Technological advances have had a significant impact on various aspects of life, including law and public administration. One important aspect is the implementation of taxation, which is a strategic strategy with high economic value and is considered an important object in economic activities. The Indonesian government has implemented an Electronic Tax Service (HT-el) system to improve efficiency, transparency, and accountability in tax administration. HT-el covers various tax-related processes, such as tax collection, creditor changes, and tax collection audits, which can be carried out electronically through an online platform. Digitalization offers many benefits, such as faster processing times, increased efficiency, and reduced long-term interconnections that prevent corruption. However, the implementation of HT-el also presents challenges that cannot be ignored. These include technological infrastructure, human resource management, and electronic data knowledge. The implementation of HT-el requires comprehensive legal services, including electronic document handling, personal data protection, and legal compliance for affected parties. One of the challenges faced in the implementation of HT-el is the relationship between creditors and debtors, which can be affected by differences in data in the electronic tax system. Debtors may believe that digital data is incompatible with the old tax system, thus creating the risk of inaccurate data input or lack of clear communication mechanisms. The implementation of HT-el also involves exploring various aspects of technology in the process, analyzing its impact on taxation, and providing recommendations for developing a better system during the data collection period. This study aims to contribute to understanding the digitalization of the tax law system and addressing the various challenges faced in its implementation.